Multimedia interaktif pecahan untuk pembelajaran matematika pada siswa kelas IV SDN Gadang 1 Malang - Nur Farida; Sri Rahayu (Math Didactic: Jurnal Pendidikan Matematika, 2017)
One of the areas of education in elementary school is mathematics. Mathematics is considered as the most difficult subject by the students in general. This case due to mathematics is demanding to think hard and abstract so that students are difficult to understand. The basic concept of mathematics is an important basic principle to support student achievement, one of them is the fractional material. Fractions are the basic material in in mathematics subject lesson for elementary school. It is expected that fractions as the basic reference of the other knowledge, thus it is very important to learn. Based on the observation,if the teacher uses the original media, students' activities are still less active even the students often play with the media that has been given by the teacher. Through the interactive multimedia, mathematics learning process is expected to be more interesting, students are motivated to follow the learning process in mathematics subjects at SDN Gadang 1 Malang.This research aims to find and describe fractions interactive multimedia in learning mathematics for fourth grade students at SDN Gadang 1 Malang. The subject of this study is students of IVB class at SDN Gadang1 Malang. The data collection techniquesare observation, interview and documentation. The research approach used is descriptivequalitative. The data obtained in this research is the application of fractions interactive multimedia in learning mathematics that is analyzed by using descriptive technique done by (1) data reduction, (2) datapresentation, (3) conclusion. The results of this study indicate the application of interactive multimedia is conducive this is strengthenedifthe teacher have already mastered the classwhen teachers apply interactive multimedia, and teacher has memorized the character of students, by understanding students’ character the teachers will be easier in conditioning the class. Based on this research, it can be concluded that the teacher should make preparation before the application of multimedia in the thematic learning, then the teacher give the material to the students and demonstrates the interactive multimedia, at the end of learning process the teacher evaluates the students by giving assessment question.